The Influence of Sports Participation on Body Image, Self-Efficacy, and Self-Esteem in College Students - Ouyang, Yiyi; Wang, Kun; Zhang, Tingran; Peng, Li; Song, Gan; Luo, Jiong (Frontiers in Psychology, 2020)
Objective: To explore the relationship between body image, self-efficacy, self-esteem and sports participation by gender, grade and specialty, then to provide reference for promoting participation in sports and physical activities in college students. Methods: The undergraduate students in western China were selected as the research participants, and the participants were selected by stratified random sampling. The data were processed by SPSS19.0 and AMOS 21.0 statistical software. Results: Body image was significantly positively correlated with self-efficacy, self-esteem and sports participation. Self-efficacy was significantly positively correlated with self-esteem and sports participation. Self-esteem was significantly positively correlated with sports participation. Body image had a direct positive influence on sports participation. Self-efficacy and self-esteem were established in the mediating role between body image and sports participation, and the chain mediating role of self-efficacy and self-esteem also reached a significant level. Conclusion: Body image, self-efficacy and self-esteem had significant influence on sports participation in college students. At the same time, self-efficacy, self-esteem as well as self-efficacy - self-esteem were established in the mediating effect on body image and sports participation, and self-esteem was the key factor affecting the sports participation .